1991
DOI: 10.1073/pnas.88.19.8597
|View full text |Cite
|
Sign up to set email alerts
|

Regulated expression of the GAL4 activator gene in yeast provides a sensitive genetic switch for glucose repression.

Abstract: Glucose (catabolite) repression is mediated by multiple mechanisms that combine to regulate transcription of the GAL genes over at least a thousandfold range. We have determined that this is due predominantly to modest glucose repression (4-to 7-fold) of expression of GAL4, the gene encoding the transcriptional activator of the GAL genes. GALA regulation is affected by mutations in several genes previously implicated in the glucose repression pathway; it is not dependent on GAL4 or GAL80 protein function. GALA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
163
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(169 citation statements)
references
References 29 publications
6
163
0
Order By: Relevance
“…Fragments of genomic DNA with sizes between 3.0-3.4 kb and 4.3-4.7 kb, respectively, corresponding to the size of the expected PGM2 gene (Oh and Hopper, 1990) were cloned into plasmid YEplacl81. Both gene li- (Struhl, 1986), transcription-termination signals (Zaret and Sherman, 1982), and putative binding sites for the GAL4 activator (West et al, 1984;Tajima et al, 1986) and MIGl repressor proteins (Nehlin et al, 1991;Griggs and Johnston, 1991) are printed in bold and are underlined. The active-site serine residues are marked by asterisks.…”
Section: Cloning and Characterization Of The Pgm2 Genementioning
confidence: 99%
“…Fragments of genomic DNA with sizes between 3.0-3.4 kb and 4.3-4.7 kb, respectively, corresponding to the size of the expected PGM2 gene (Oh and Hopper, 1990) were cloned into plasmid YEplacl81. Both gene li- (Struhl, 1986), transcription-termination signals (Zaret and Sherman, 1982), and putative binding sites for the GAL4 activator (West et al, 1984;Tajima et al, 1986) and MIGl repressor proteins (Nehlin et al, 1991;Griggs and Johnston, 1991) are printed in bold and are underlined. The active-site serine residues are marked by asterisks.…”
Section: Cloning and Characterization Of The Pgm2 Genementioning
confidence: 99%
“…Preference for glucose is in part due to repression of transcription of genes not required for growth on glucose, such as genes encoding enzymes for converting other carbon sources to glycolytic intermediates (e.g., GAL and SUC), gluconeogenesis (e.g., FBP1 and PCK1), and respiration (e.g., CYCI and COX6) (for reviews, see Johnston and Carlson, 1992;Trumbly, 1992;Ronne, 1995). Migl is the repressor responsible for glucose repression of many genes, including GAL, SUC, and MAL (Nehlin and Ronne, 1990;Griggs and Johnston, 1991;Nehlin et al, 1991;Schuller and Entian, 1991;Flick and Johnston, 1992;Johnston et al, 1994;Vallier and Carlson, 1994;Hu et al, 1995;Lutfiyya and Johnston, 1996;Wang and Needleman, 1996). Migl is a Cys2-His2 zinc finger-containing protein that binds to promoters of glucose-repressed genes and recruits the general repressors Ssn6 and Tupl Struhl, 1994, 1995;Treitel and Carlson, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Since the level of GAL4 expression is rate-limiting for the induction of GAL gene expression (Griggs and Johnston, 1991) and the expression of GAL4 itself is under the control of IMP2, we tested whether imp2 glucose repressible phenotype was influenced by GAL4 gene dosage.…”
Section: Gal4 Overexpression Partially Suppresses the Imp2 Glucose-rementioning
confidence: 99%
“…Gal4p is in turn glucose-regulated (Laughon and Gesteland, 1982;Griggs and Johnston, 1991;Nehlin et al, 1991). It has been demonstrated that modest glucose repression (four-to seven-fold) of GAL4 is the predominant cause of glucose repression of GAL genes (Griggs and Johnston, 1991). Mig1p is mainly responsible for glucose repression of GAL genes (Nehlin et al, 1991;Flick and Johnston, 1992;Johnston et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation